2010
DOI: 10.1016/j.ydbio.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Tenectin is a novel αPS2βPS integrin ligand required for wing morphogenesis and male genital looping in Drosophila

Abstract: Morphogenesis of the adult structures of holometabolous insects is regulated by ecdysteroids and juvenile hormones and involves cell-cell interactions mediated in part by the cell surface integrin receptors and their extracellular matrix (ECM) ligands. These adhesion molecules and their regulation by hormones are not well characterized. We describe the gene structure of a newly described ECM molecule, tenectin, and demonstrate that it is a hormonally regulated ECM protein required for proper morphogenesis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 108 publications
(132 reference statements)
3
25
0
Order By: Relevance
“…As mentioned above, tnc encodes an extracellular matrix protein involved in cell adhesion. Consistent with a role for tnc in mediating adhesion between the dorsal and ventral surfaces of the wing pouch, RNAimediated knockdown of tnc results in defects in wing morphology (Fraichard et al 2010). We cloned two temporally dynamic open chromatin sites located ∼40 kb upstream of the tnc promoter.…”
Section: Temporally Dynamic Open Chromatin Sites Correspond To Tempormentioning
confidence: 78%
See 1 more Smart Citation
“…As mentioned above, tnc encodes an extracellular matrix protein involved in cell adhesion. Consistent with a role for tnc in mediating adhesion between the dorsal and ventral surfaces of the wing pouch, RNAimediated knockdown of tnc results in defects in wing morphology (Fraichard et al 2010). We cloned two temporally dynamic open chromatin sites located ∼40 kb upstream of the tnc promoter.…”
Section: Temporally Dynamic Open Chromatin Sites Correspond To Tempormentioning
confidence: 78%
“…S2A). For example, the tenectin gene (tnc), which encodes a constituent of the extracellular matrix that binds α-PS2 integrin (Fraichard et al 2010), exhibits multiple open chromatin changes between L3, 24-h, and 44-h wings ( Fig. 2A).…”
Section: Open Chromatin Profiles Are Temporally Dynamic In Pupal Wingsmentioning
confidence: 99%
“…It encodes an integrin binding protein related to developmental processes and is regulated by ecdysone during wing development. Transcripts for this gene were recently identified in Drosophila leg discs, eye and brain ( Fraichard et al , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that rhea/talin and mys are involved in integrin adhesion suggests an important role of cell-extracellular matrix (ECM) adhesion for genitalia LR asymmetry. Of note, mutations in the Drosophila tenectin gene, encoding a ligand for PS2 integrin, can induce genitalia rotation defects [32], and recent work showed that genitalia rotation involves cell intercalation and asymmetry of junction remodeling [31]. A role for cell adhesion and ECM has also been shown in vertebrates for LR asymmetry.…”
Section: Actin Nucleation Cell Polarity and Cell Adhesion Are Importmentioning
confidence: 99%